Intracranial Meningeal Involvement in Churg-Strauss Syndrome - Tokumaru, Aya M. (AJNR Am J Neuroradiol, 2002)
Summary: We describe the case of a 54-year-old woman with a clinical diagnosis of Churg-Strauss syndrome (CSS). The patient had a fever of unknown origin, severe headache, progressing left ophthalmoplegia, and visual acuity disturbance. MR imaging revealed diffuse and thick hypointense lesions on T2-weighted images in the frontal meninges and anterior falx cerebri with diffuse enhancement. Similar lesions were also detected in the left superior ophthalmic fissure to the cavernous sinus. Nodular lesions in the fourth ventricle, which might have been the cause of hydrocephalus, were hypointense on T2-weighted images. These MR imaging findings suggested remote granulomatous involvement in the meninges and choroid plexus associated with CSS. To our knowledge, remote meningeal involvement in association with CSS has not been previously reported.